Answer:
Given the function f(x) = 3x + 1, evaluation of f(a + 1) gives:
C. 3a + 4
Step-by-step explanation:
Given function:
f(x) = 3x + 1
We have to find f(a+1).
For this purpose, we will take x = a+1 and
substitute it in the function f(x) = 3x+1:
f(x) = 3x + 1
f(a+1) = 3(a+1) +1
f(a+1) = 3(a) + 3(1) +1
f(a+1) = 3a+3+1
f(a+1) = 3a + 4
So the function f(a+1) is equal to option C. 3a + 4.
Answer:
What is the question is this Geometry?
Step-by-step explanation:
Answer:
b is the answer
Step-by-step explanation:
I took the test
Answer:
0.4
Step-by-step explanation:
1/4 = 0.25
Answer:
Trapezoid
Step-by-step explanation:
HOPE THIS HELPS
PLZZ MARK BRAINLIEST